Evaluation of anisotropic correction models for diffuse solar irradiance measured by the MEO shadow ring method - Dal Pai, Alexandre [UNESP]; Dal Pai, Enzo [UNESP]; Sarnighausen, Valéria Cristina Rodrigues [UNESP]; Escobedo, Joaõ Francisco [UNESP] (AIP Publishing, 2020)
Diffuse solar radiation is measured using a pyranometer positioned under the shadow of a ring. The function of the ring is to block direct solar radiation. However, the ring also blocks a portion of the diffuse solar radiation, and therefore, the diffuse radiation needs corrections. The most well-known assembly in the literature on the shading ring method is the Drumond assembly. This study aims to determine the effectiveness of three methods of correction of diffuse irradiance measured with shadow bands: The LeBaron method, the Battles method, and the Dal Pai method. The Laboratory of Solar Radiometry of Botucatu provided global, direct, and diffuse solar irradiances. The laboratory measures diffuse solar radiation using the Melo-Escobedo-Oliveira (MEO) shading ring method, a different setup compared to Drummond's setup. The period used for the study comprised the years 1996 to 2005. The results showed that LeBaron and Battles correction models with the original coefficients are not suitable for correction of diffuse irradiance in Botucatu. According to MBE (Mean Bias Error) and RMSE (Root Mean Square Error), the statistical indicators, LeBaron and Battles with adjusted coefficients, and Dal Pai correction models are indicated to correct the diffuse irradiance in Botucatu measured under an MEO shading ring. For monthly applications, the LeBaron model with adjusted coefficients is recommended. Although this model is more complex from the operational point of view, it better explains anisotropic effects, especially for the winter months.